Frecuencia y factores de riesgo de consumo de sustancias psicoactivas en estudiantes de derecho de la Universidad Nacional de Loja - Guerra Flores, Daniela Luisangie (2022)
The consumption of PAS (psychoactive substances) has a significant impact on the lives of young people; determining the frequency with which they maintain consumption behaviors and the circumstances to which they are exposed while repeating these patterns, allow us to discern some specific points in which we can contribute to the comprehensive development of our group, addressing the situation that enhances their states of consumption . A descriptive, quantitative, retrospective cross-sectional study was carried out, entitled: "Frequency and risk factors for the consumption of psychoactive substances in law students of the National University of Loja", with a sample of 130 students from October 2020 to March 2020. 2021. The Drug Abuse Assessment (GAP) was applied in relation to the frequency and risk factors related to PAS consumption. The results of this study showed that 55% of the respondents are between the ages of 21 and 25. In 56% the female sex predominates; 81% correspond to the urban area, 98% are single and in the same proportion belong to the mestizo ethnic group. Regarding the type and frequency of PAS consumption, 100% have never used heroin in their lives and 6% have never consumed alcohol; 85% have consumed alcohol in the last 6 months, 61% in the same period of time have used tobacco and 29% marijuana, while in the last 30 days 67% have drunk alcohol, 28% have used tobacco and 12% have used marijuana. Within the risk factors of consumption, in 61% there was the presence of traits of family dysfunction, 81% of the students have not perceived any type of abuse, while 18% have been victims of psychological abuse at some point. of their life. 50% at some point in their life were invited to consume SPA by a member of their family environment, 76% have felt pressure from their peer group to consume SPA and in 80% socializing is the main reason for consumption . 86% indicate that it is accessible in relation to the cost to acquire SPA. 68% receive information promoting SPA consumption on social networks; 88% mention that there is a lack of information on the short and long-term effects of SPA consumption, 57% of the sample doubts about the existence of SPA consumption prevention programs.